2008
DOI: 10.1177/0273475308322282
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Team Personality Awareness Exercises on Team Satisfaction and Performance

Abstract: Marketing courses heavily utilize team projects that can enhance student learning and make students more desirable to recruiters seeking greater teamwork skills and experience from students. Unfortunately team projects that provide opportunities to learn and improve such skills can also be great sources of frustration and dissatisfaction for instructors and students. This research investigates the effects of exercises designed to encourage student reflection on their behavior as team members and engage in proa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…(The McAllister (1995) scales are readily available in the literature. Two items from the scale measuring satisfaction with teammates (Lancellotti and Boyd (2008) are: 1. My teammates approach the mission with professionalism and dedication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(The McAllister (1995) scales are readily available in the literature. Two items from the scale measuring satisfaction with teammates (Lancellotti and Boyd (2008) are: 1. My teammates approach the mission with professionalism and dedication.…”
Section: Methodsmentioning
confidence: 99%
“…Team satisfaction was assessed using a team satisfaction scale adapted from Lancellotti and Boyd (2008). The scale contained three items, which assessed individual desire to be a part of the team (Cronbach's α = 0.85-0.88).…”
Section: Team Satisfactionmentioning
confidence: 99%
“…For example, Emery and Barker (2007) found team structures increased productivity and net profit. When aggregated, higher team satisfaction scores led to increased team performance (Lancellotti & Boyd, 2008). However, there are also studies that have found that teams can have a negative effect.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Repeated administrations of peer feedback provide the time that students need to absorb the feedback and develop self-awareness (Mayo, Kakarika, Pastor, & Brutus, 2012). This may enhance self-regulation and encourage team members to discuss problems with one another, which tends to improve students' satisfaction with the team and may improve team performance (Lancellotti & Boyd, 2008). Repeated administrations of peer evaluations with a standardized instrument also build students' confidence at rating their teammates and improves the quality of their peer evaluations (Brutus, Donia, & Ronen, 2013).…”
Section: Catme Peer Evaluationmentioning
confidence: 99%
“…We cited evidence in this paper that using a consistent peer evaluation system repeatedly and providing multiple rounds of feedback have benefits for students, including learning to rate teamwork better, improving team skills, and developing better self-awareness. (Brutus & Donia, 2010;Brutus, Donia, & Ronen, 2013;Lancellotti & Boyd, 2008;Mayo, Kakarika, Pastor, & Brutus, 2012). These studies, however, were conducted with other peer evaluation systems.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%